Palaeoceanographic and environmental changes in the eastern Fram Strait during the last 14,000 years based on benthic and planktonic foraminifera - Consolaro, Chiara; Rasmussen, Tine Lander; Panieri, Giuliana (Marine Micropaleontology, 2017)
Submitted manuscript version. Published version available at https://doi.org/10.1016/j.marmicro.2017.11.001 . Submitted manuscript version, licensed CC BY-NC-ND 4.0. Benthic and planktonic foraminifera, stable isotopes and other geochemical and sedimentological parameters have been investigated in a sediment core from Vestnesa Ridge (79°N, NW Svalbard margin, 1300 m water depth) in order to reconstruct the palaeoceanographic and palaeoenvironmental evolution of the eastern Fram Strait during the last 14,000 years. Our multiproxy data and, in particular, our high-resolution benthic foraminiferal record allow a detailed reconstruction of the intermediate water flow in the eastern Fram Strait. During the Bølling-Allerød warm interstadials the high proportion of the benthic Atlantic species Cassidulina neoteretis suggests the presence of chilled Atlantic-derived water at the bottom of the Vestnesa Ridge, while the dominance of the polar planktonic species Neogloboquadrina pachyderma (s) indicates cold polar surface conditions. During the Younger Dryas cold stadial the inflow of Atlantic-derived water was weakened and of lower temperature compared to the previous interval, as suggested by the increase in the glacio-marine indicator Cassidulina reniforme and the lower percentages of C. neoteretis . After 11,000 cal yr BP the abrupt increase in relative abundance of the benthic species Cibicides wuellerstorfi and Oridorsalis umbonatus , indicates a shift to interglacial conditions with deep convection and generation of cold intermediate water. Warm surface water conditions were finally established at about 10,300 cal yr BP, when Turborotalita quinqueloba became the dominant planktonic species. Generally warmer conditions than today were recorded in the middle Holocene, with a mild cooling at about 8200 cal yr BP and a more pronounced cool interval with an abrupt decrease in T. quinqueloba between 7000 and 6200 cal yr BP. Cold climatic conditions were established around 4100 cal yr BP when N. pachyderma (s) became ...